Labyrinths of the emancipation. Reciprocity and conflict between agents of social development and peasants leaders - Cowan Ros, Carlos Javier (Revista de Antropología Social, 2013)
This paper analyzes the relationship between the professional team members of a NGO in the field of social development, and the leaders of an organisation of peasants and aboriginal, located in the province of Jujuy, northwest of Argentina. The link itself is interpreted as a relationship of cultural mediation, which is constructed through a cycle of social provisions —in terms of free benefits— which involves a net of expectations and commitments —not always honoured—. These links expose one of the paradoxes of social development, which constitutes the main object of empirical analysis and theoretical reflection of this paper. This kind of bond shows a certain ambiguity: if, on the one hand, the agents of social promotion aim a better position in terms of autonomy and emancipation for the target group of their actions, on the other hand, through the kind of bond they build and as a consequence of the sort of power they exert, they tend to generate some dependence with the institutions they represent. This contradiction is manifested through tensions and disputes that, when develop, result on reconfigurations of the bond itself, and of the social organisations they work with.
Keywords: Cultural mediation; peasantry; social promotion; social reproduction strategies